Complexity of Purchasing Decisions: The Role of Brand Image, Viral Marketing and Purchase Interest - Nareswari, Ayu; Azizah, Yuliatin (Bulletin of Management and Business, 2024)
In the era of globalization and intensifying market competition, purchasing decisions have become crucial in product or service marketing strategies. The complexity of these decisions is a central focus for researchers and business practitioners seeking to understand dynamic consumer behavior. Brand image, viral marketing, and purchase interest play key roles in shaping these decisions. Brand image shapes consumer perceptions, while viral marketing effectively introduces products or services to broad audiences. Purchase interest reflects consumer desires and intentions. This study investigates the relationship between these factors and their impact on purchasing decisions in the Indonesian market, focusing on Store Cabang Jember dan Lumajang as a case study. Using quantitative methods, data was collected through questionnaires from 100 respondents. Results show significant influences of brand image, viral marketing, and purchase interest on purchasing decisions. These findings provide valuable insights for companies designing effective marketing strategies to navigate dynamic market challenges, particularly in Jember dan Lumajang's fashion industry. The research utilizes smart partial least squares (PLS) for data analysis. The study concludes that while brand image does not significantly influence purchasing decisions, viral marketing and purchase interest positively and significantly impact these decisions.